DEVELOPMENT OF SCIENCE TEACHING AIDS USING RECYCLED MATERIALS TO IMPROVE STUDENTS' CRITICAL THINKING SKILLS - Lili Kasmini; Reni Reni; Safrina Junita; Zahria Amalina (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
The Low Critical Thinking Skills of Fourth Grade Students at SDIT Nurul Ishlah and the Lack of Effective Learning Media and Teaching Aids are the Background of This Research. The purpose of this research is to measure the validity, analyze the practicality, and determine the effectiveness of science teaching aids made from recycled materials in improving students' critical thinking skills. The method used is Research and Development (R&D) with the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The results of the research indicate that the science teaching aids made from recycled materials were assessed as highly valid, with a percentage of 95.56% from media experts and 97.78% from material experts. In terms of practicality, the teaching aids were considered very practical, with a 94% rating from teachers. The effectiveness test using the One Sample T-Test produced a p-value of 0.05, indicating that these teaching aids are effective in improving students' critical thinking skills. Furthermore, the N-Gain test showed a score of 72.42%, indicating a high level of improvement in students' critical thinking skills. Overall, the science teaching aids made from recycled materials have been proven to be highly valid, practical, and effective in supporting the learning process and enhancing students' critical thinking skills.